A2T and A2V Aβ peptides exhibit different aggregation kinetics, primary nucleation, morphology, structure, and LTP inhibition. Issue 4 (23rd February 2016) - Murray, Brian; Sorci, Mirco; Rosenthal, Joseph; Lippens, Jennifer; Isaacson, David; Das, Payel; Fabris, Daniele; Li, Shaomin; Belfort, Georges
ABSTRACT: The histopathological hallmark of Alzheimer's disease (AD) is the aggregation and accumulation of the amyloid beta peptide (Aβ) into misfolded oligomers and fibrils. Here we examine the biophysical properties of a protective Aβ variant against AD, A2T, and a causative mutation, A2T, along with the wild type (WT) peptide. The main finding here is that the A2V native monomer is more stable than both A2T and WT, and this manifests itself in different biophysical behaviors: the kinetics of aggregation, the initial monomer conversion to an aggregation prone state (primary nucleation), the abundances of oligomers, and extended conformations. Aggregation reaction modeling of the conversion kinetics from native monomers to fibrils predicts the enhanced stability of the A2V monomer, while ion mobility spectrometry‐mass spectrometry measures this directly confirming earlier predictions. Additionally, unique morphologies of the A2T aggregates are observed using atomic force microscopy, providing a basis for the reduction in long term potentiation inhibition of hippocampal cells for A2T compared with A2V and the wild type (WT) peptide. The stability difference of the A2V monomer and the difference in aggregate morphology for A2T (both compared with WT) are offered as alternate explanations for their pathological effects. Proteins 2016; 84:488–500. © 2016 Wiley Periodicals, Inc.